2008
DOI: 10.1016/j.jhep.2008.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral virus-specific T-cell interleukin-10 responses develop early in acute hepatitis C infection and become dominant in chronic hepatitis

Abstract: Background & Aims-Interleukin-10 (IL-10) has been ascribed pro-viral but anti-fibrotic properties in chronic hepatitis C virus (HCV) infection. In this study, we examined the role of HCVspecific T-cell IL-10 response in patients with acute and chronic HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
4
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 62 publications
4
58
4
1
Order By: Relevance
“…In agreement with the well-known immunomodulatory activity of IL-10 in several tissues, several studies have reported a role for IL-10 as a protective cytokine against hepatic injury in diseases such as diet-induced insulin resistance in liver (Cintra et al, 2008), experimental hepatitis induced by LPS (Santucci et al, 1996) and concanavalin A (Louis et al, 1997), schistosomiasis (Winn et al, 1998), alcoholic hepatitis (Le Moine et al, 1995), hepatitis C virus infection (Kaplan et al, 2008) and fatty liver disease (Den Boer et al, 2006). The immunosuppressive cytokine IL-10 is crucial for tolerance induction in concanavalin A-induced liver damage in mice and is mainly expressed by CD4 + CD25 + regulatory T cells (Erhardt et al, 2007).…”
Section: The Antiinflammatory Cytokine Il-10 Is Regulated By Nf-kb1 (supporting
confidence: 52%
“…In agreement with the well-known immunomodulatory activity of IL-10 in several tissues, several studies have reported a role for IL-10 as a protective cytokine against hepatic injury in diseases such as diet-induced insulin resistance in liver (Cintra et al, 2008), experimental hepatitis induced by LPS (Santucci et al, 1996) and concanavalin A (Louis et al, 1997), schistosomiasis (Winn et al, 1998), alcoholic hepatitis (Le Moine et al, 1995), hepatitis C virus infection (Kaplan et al, 2008) and fatty liver disease (Den Boer et al, 2006). The immunosuppressive cytokine IL-10 is crucial for tolerance induction in concanavalin A-induced liver damage in mice and is mainly expressed by CD4 + CD25 + regulatory T cells (Erhardt et al, 2007).…”
Section: The Antiinflammatory Cytokine Il-10 Is Regulated By Nf-kb1 (supporting
confidence: 52%
“…Two skin biopsies (day 5 or 7 and day 9) and two axillary LN biopsies (weeks 1 and 2) were obtained from each monkey. Peripheral blood samples, as well as oral and genital swabs, were collected longitudinally after challenge (weekly for week 0-12, biweekly for week 12-28, monthly for week [28][29][30][31][32][33][34][35][36][37][38][39][40]. Blood samples were processed for PBMC and plasma.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Ulsenheimer [53] showed that HCV antigen-specific Tr1 and Th3 cells were detected in the peripheral blood of acute HCV patients. In another study, Kaplan et al [54] demonstrated a broad HCV-specific Tr1 response that was induced during early acute hepatitis with reduced HCV-specific CD4? T-cell proliferation and increased HCV viremia.…”
Section: Regulatory T Cellsmentioning
confidence: 98%